ACTIVATION OF ZEOLITE WITH ULTRASONIC WAVE FOR ADSORPTION RECTIVE YELLOW 86 ON SAMARINDA WASTE WOVEN - Ronaldy, Igo Marsat; Hindryawati, Noor; N. S, R. R. Dirgarini Julia (Jurusan Kimia FMIPA UNMUL, 2017)
The research about activation of natural zeolite with variation concentration HCl for adsorption reactive yellow 86 from waste liquid woven Samarinda has been conducted. The activation of zeolite was prepared with two way, by mechanicalstirring and ultrasonic assisted. From the X-Ray Diffraction (XRD) result showed that natural zeolite activated with ultrasonic (NZA-U) has 38 % composition of SiO2, while natural zeolite activated with mechanical stirring (NZA-MS) is 21 %. Surface area analysis using methylene blue shows for NZA-U is 25 m2/g and 24 m2/g for NZA-MS. The results on adsorption of reactive yellow 86 from waste liquid woven Samarinda using spectrophotometer visible on wavelength 417 nm shows the optimum condition adsorption on time contact60 minutes and concentration HCl 3 M, with percent of adsorption is 56.14 % for NZA-U and 53.93 % for NZA-MS